1999
DOI: 10.1111/j.1468-3083.1999.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma secondary to recessive dystrophic epidermolysis bullosa: report of eight tumours in four patients

Abstract: The patients consulted too late and their large lesions needed aggressive treatment. Appropriate information and regular examination of patients with RDEB helps early diagnosis of tumours and may avoid disabling operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…5 As with actinically induced SCCAs, they often present as hyperkeratotic nodules but can be very large, sometimes growing to an 18-cm mass over six months. 6 Our patient developed a 4-cm ulcer on the right knee that proved on histologic examination to be a moderately differentiated SCCA. Its surface did not show hyperkeratosis but was filled with heaped-up granulation tissue like material.…”
Section: Discussionmentioning
confidence: 96%
“…5 As with actinically induced SCCAs, they often present as hyperkeratotic nodules but can be very large, sometimes growing to an 18-cm mass over six months. 6 Our patient developed a 4-cm ulcer on the right knee that proved on histologic examination to be a moderately differentiated SCCA. Its surface did not show hyperkeratosis but was filled with heaped-up granulation tissue like material.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the fact that SCCs in RDEB are usually histologically well differentiated, they often have a poor prognosis because of the high frequency of occurrence, rapid invasiveness, and development of distant metastases 3 . They are also often multiple 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…The cumulative risks for death from SCC in RDEB‐HS and all other RDEB subtypes by age 45 are 55.2% and 12.8%, respectively 8 . Although the SCC that arise in RDEB are typically well‐differentiated, these lesions can exhibit rapid proliferation and frequent metastasis 9 . The presence of regional lymph node metastasis is the most important prognostic factor for the majority of solid tumors, including SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that SNB can detect subclinical lymph node metastasis in patients with high‐risk cutaneous SCC 7 . RDEB patients should be classified to this group because of the aggressiveness of associated SCC 9 . Previously, SNB has been applied to patients with occult regional lymph node metastasis; those patients displaying clinically overt lymphadenopathy have typically undergone complete lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%